Digital Water Accounting for Value Creation, Transforming Water Data into Strategic Sustainability Assets - Renaldo, Nicholas; Fransisca, Luciana (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This paper offers a novel contribution by positioning digital water accounting as a value creation mechanism across multiple dimensions, economic, environmental, and strategic. It examines not only the technologies enabling this shift but also how digital water insights unlock opportunities in the circular economy, mitigate risk, and foster stakeholder trust. Given the emerging nature of digital water accounting and its integration with sustainability strategies, a qualitative case study method is appropriate. This approach allows for an in-depth exploration of complex systems, real-world challenges, and the interplay between technology, data, and organizational value. This study demonstrates that Digital Water Accounting (DWA) is more than a technological upgrade to traditional water management, it is a strategic innovation that drives multidimensional value creation. By integrating digital tools such as IoT sensors, cloud computing, and analytics, DWA enables organizations to optimize water use, reduce costs, comply with regulations, improve ESG reporting, and unlock new opportunities in sustainability and circular economy practices. Future studies should incorporate larger datasets and econometric methods to quantify the financial and sustainability impacts of DWA systems.